Entrepreneurship Education and Training : Insights from Ghana, Kenya, and Mozambique - Robb, Alicia; Valerio, Alexandria; Parton, Brent (Washington, DC: World Bank, 2014)
This report summarizes the key themes and findings from three in-depth case studies of EET programs in Ghana, Kenya, and Mozambique. Each case study produced rich information on the programs context, the landscape of programs in each country, and the qualitative insights from local EET stakeholders. This report synthesizes information from across the case studies to analyze the extent to which these countries programs are meeting the needs of local entrepreneurs. It also introduces findings from global EET research to show how programs in the case-study countries relate to what is known about global practice in EET. From this synthesis, the report presents a set of key findings intended to illuminate how EET programs can be better aligned with local needs and promising EET practices globally.